A two-pore channel protein required for regulating mTORC1 activity on starvation - Chang, F; Wang, Y; Dmitriev, P; Gross, J; Galione, A; Pears, C (BioMed Central, 2020)
Background Two-pore channels (TPCs) release Ca2+ from acidic intracellular stores and are implicated in a number of diseases, but their role in development is unclear. The social amoeba Dictyostelium discoideum proliferates as single cells that aggregate to form a multicellular organism on starvation. Starvation is sensed by the mTORC1 complex which, like TPC proteins, is found on acidic vesicles. Here, we address the role of TPCs in development and under starvation.